(untitled) - Butz, Stephen D. (Australia, 2015)
The use of agriculturally based fuel systems, also known as biofuels, as a means to supply energy to our technological society, provides environmentally safe, renewable energy options for all aspects of life, including industry, transportation, and electrical power generation. By providing a solid foundation in the energy and resources used historically combined with a look at future options toward more sustainable resources ENERGY AND AGRICULTURE provides a solid understanding of one of the most important issues of the twenty-first century.
Keywords: Năng lượng tái sinh,Renewable energy sources,Sustainable buildings